Analisis Penggunaan Kembali Map Rekam Medis dalam Upaya Memperoleh Efisiensi Biaya di Siloam Hospitals Surabaya - Tri Murni M; Ina Suhartina; Fransiskus W (Jurnal Kesehatan Vokasional, 2018)
Background: Inactive medical records are files that have been kept for at least 5 years in the medical record work unit since the last date the patient is served at the health services facility or 5 years after death. There are several stages in inactive medical records; it begins from sorting and moving from active shelves to inactive shelves. Then, there will be sorting of files that can be destroyed, the process of transferring the media, and destroying process. This process of inactive medical records produces waste paper that will be destroyed. This waste paper can still be used if it is recycled. Re-Use Folder is invented to recycle paper waste so that it can be reused.Objective: This study aims to analyze the medical record folder that can be reused.Method: This research will use descriptive results of the analysis of the use of the Re-Use Folder and to explain the results of estimated hospital expenses after using the Re-Use Folder.Results: Siloam Hospitals Surabaya spent Rp. 92,875,000.00 (81%) of routine medical records in 2016. It is expected to reduce cost after using Re-Use Folder per month to be Rp. 7,673,333.00. Thus the problem of unavailability of human resource will also be solved. So that several benefits will obtained, such as: running retention, cost efficiency, larger storage, and reduces environmental pollution.Conclusion: Based on the results of the research conducted, the use of the Re-Use Folder can improve the efficiency of the production process so that production costs can be reduced.